International Congress on Energy Efficiency and Energy Related Materials (ENEFM2013) Proceedings, Antalya, Turkey, 9-12 October 2013 - Oral, Ahmet Yavuz; Bahsi, Zehra Banu; Ozer, Mehmet (Springer Proceedings in Physics, 2014)
The International Congress on Energy Efficiency and Energy Related Materials (ENEFM2013) was held on 9-12 October, 2013. This three-day congress focused on the latest developments of sustainable energy technologies, materials for sustainable energy applications and environmental & economic perspectives of energy. These proceedings include 63 peer reviewed technical papers, submitted from leading academic and research institutions from over 23 countries, representing some of the most cutting edge research available. The papers included were presented at the congress in the following sessions: General Issues Wind Energy Solar Energy Nuclear Energy Biofuels and Bioenergy Energy Storage Energy Conservation and Efficiency Energy in Buildings   Economical and Environmental Issues Environment Energy Requirements Economic Development   Materials for Sustainable Energy Hydrogen Production and Storage Photovoltaic Cells Thermionic Converters Batteries and Superconductors Phase Change Materials Fuel Cells Superconductors.